2020
DOI: 10.1016/j.ijbiomac.2020.07.167
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin, a unique molecule with diverse therapeutical and nanotechnological applications

Abstract: Lactoferrin (LF) is a naturally glycoprotein with iron-binding properties and diverse biological applications including; antiviral, anti-inflammatory, antioxidant, anti-cancer and immune stimulating effects. In addition, LF was found to be an ideal nanocarrier for some hydrophobic therapeutics because of its active targeting potential due to overexpression of its receptor on the surface of many cells. Moreover, it was proven to be a good candidate for fabrication of nanocarriers to specifically deliver drugs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 119 publications
(204 reference statements)
0
38
0
Order By: Relevance
“…Dietary Lf, included in both natural and supplemented foods, incurs in both enzymatic digestion and physical barriers of the gastrointestinal mucosa, which contribute to its poor permeability across the gut epithelium. To overcame this drawback, two strategies have been carried out: the administration of purified Lf (usually bLf) at higher dosage and, more recently, the development of new formulations of Lf aimed at improving its bioavailability [ 285 ]. In this regard, despite several studies have proven Lf to be safe and well-tolerated even at high dosages [ 286 , 287 ], Nguyen et al reported that the effect of bLf on the inflammatory balance of both intestinal epithelial cells and immature pig intestine is strictly dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary Lf, included in both natural and supplemented foods, incurs in both enzymatic digestion and physical barriers of the gastrointestinal mucosa, which contribute to its poor permeability across the gut epithelium. To overcame this drawback, two strategies have been carried out: the administration of purified Lf (usually bLf) at higher dosage and, more recently, the development of new formulations of Lf aimed at improving its bioavailability [ 285 ]. In this regard, despite several studies have proven Lf to be safe and well-tolerated even at high dosages [ 286 , 287 ], Nguyen et al reported that the effect of bLf on the inflammatory balance of both intestinal epithelial cells and immature pig intestine is strictly dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LfRs are overexpressed on the cellular surface of glioma [ 171 ], thus augmenting the specific uptake of Lf by cancer cells. There is sufficient evidence to support this concept, especially in gliomas [ 172 ]. Alternatively, Lf might be secreted by neoplastic astrocytes [ 171 ].…”
Section: Lf In Other Neurological Diseasesmentioning
confidence: 99%
“…As a major iron-binding protein found in milk and other body fluids, Lf exerts antibacterial, antiviral, anti-inflammatory, immune-modulatory and anticarcinogenic effects [ 1 ]. Because of its ability to cross the BBB through LfR-mediated transcytosis processes within brain capillary endothelial cells [ 44 , 56 ] and its relatively good biocompatibility, safety, stability and resistance to proteolysis [ 5 ], the use of exogenous Lf as a therapeutic agent or the use of drug-loaded Lf-based nanoparticles were explored for the treatment of neurodegenerative diseases, cerebrovascular diseases, childhood developmental delays, brain tumors and other neurological-related diseases [ 57 , 172 , 173 ]. In fact, several unsolved questions emerge from studies including the bioavailability of Lf after oral administration, differences in physicochemical properties of commercially available Lf (in particularly the iron content), and difficulties in the clinical application (dosage, durations, evaluation of the outcomes), although it exerts pleiotropic biological functions and is safe and low-cost as a potential therapeutic agent [ 5 , 174 ].…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…These data suggest the role of Ltf in ferroptosis is complicated: it may depend on iron saturation statues (apo or holo form) of Ltf, and it may also have cell-specificity. Importantly, Ltf accesses the blood bran barrier (BBB) via receptor-mediated transcytosis, because Ltf receptors are highly expressed on the surface of the brain endothelial cells [ 75 , 76 ]. Additionally, research shows that orally and intravenously administered recombinant human Ltf had similarities in the up-regulation of specific genes involved in oxidative stress and inflammatory responses for both routes of treatments [ 77 ].…”
Section: Discussionmentioning
confidence: 99%